An electronic laager: a sculptural interpretation of post-industrial society's cybernetic order - van der Schijff, Johann (Michaelis School of Fine Art, 2023)
There is the need to express what it is like to be a feeling, thinking, young person growing up on the southern tip of the African continent today, and this, from a generation who have had to cope with and survive the pressures of brain washing or intellectual laundering that an education in a State school in South Africa usually enforces. It is a generation trying to come to terms with information that has been filtered through the organs of the State radio and television systems, which routinely exclude news not deemed to be in the public interest, and substitutes an iconology dedicated to the values of sunny skies, beer and braaivleis. (Dubow 1986: 60) As an artist living in South Africa, I am part of the generation that has had to cope with the 'intellectual laundering' Dubow speaks of. I have experienced the ways in which apartheid, as a cultural norm governing society, has been constructed. It is around these issues that the title, An electronic laager: A sculptural interpretation of post-industrial society's cybernetic order, forms a concise description, and 'key' to an interpretation and understanding of the various issues which have amalgamated to inform my iconography, and the way in which these issues have been transformed into sculptural expression.